Analisis Faktor Knowledge Inertia Sebagai Anteseden Penciptaan Daya Saing Individu Wirausahawan - Honesty Sinurat; Hafiz Rahman; Donard Games (SAFE-Network, 2023)
The purpose of this study is to explore the existence of knowledge inertia as an antecedent of creating individual competitiveness for nascent entrepreneurs and mature entrepreneurs. As well as what are the differences between nascent and mature entrepreneurs regarding mastery of knowledge and facts regarding the existence of knowledge inertia. This research uses a qualitative method using the comparative case studies method which aims to obtain a clear picture of a problem, which focuses on collecting data or information on objects. The results of the research findings and the results of the analysis of Project Map NVivo 12 plus, nascent entrepreneurs are more likely to experience inertia due to limited capital, limited human resources, fear of trying new things, lack of business relationships, lack of employee competency, and limited experience because they are still beginners in running their business. Meanwhile, mature entrepreneurs have a smaller tendency of inertia compared to nascent entrepreneurs. This is because as an old player and more experienced in maintaining the stability of its business so that it focuses more on maintaining its competitive position by having to be able to adapt to the times to achieve competitive advantage.